Secret-Word by e-Abacus Diagram I - Mahmood, Awreng B.; Mahmood, Ammar S. (Iraqi Journal of Science, 2019)
This experiment may be applied before with certain and special roles, but never applied under partition theory (Abacus James Diagram) conditions. Therefore, we would have to find an appropriate design for each character to enable us sending a word represented as increasing number with meaning only for beneficiaries.